2017
DOI: 10.1038/s41598-017-11423-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for raw meat to influence human colonization with Staphylococcus aureus

Abstract: The role of household meat handling and consumption in the transfer of Staphylococcus aureus (S. aureus) from livestock to consumers is not well understood. Examining the similarity of S. aureus colonizing humans and S. aureus in meat from the stores in which those individuals shop can provide insight into the role of meat in human S. aureus colonization. S. aureus isolates were collected from individuals in rural and urban communities in Iowa (n = 3347) and contemporaneously from meat products in stores where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Prevalence rates for S. aureus of 64%, 20% and 17% were reported in raw beef, sheep and lamb samples at retail with an overall prevalence of 21% (Şanlıbaba, 2022 ). Similar studies in the United States of America, Japan and Poland isolated this bacterium from 28%, 33% and 68%, respectively (Hiroi et al., 2012 ; Krupa et al., 2014 ; Carrel et al., 2017 ). Although information on growth on meat products is limited, Phillips et al.…”
Section: Assessmentsupporting
confidence: 64%
See 1 more Smart Citation
“…Prevalence rates for S. aureus of 64%, 20% and 17% were reported in raw beef, sheep and lamb samples at retail with an overall prevalence of 21% (Şanlıbaba, 2022 ). Similar studies in the United States of America, Japan and Poland isolated this bacterium from 28%, 33% and 68%, respectively (Hiroi et al., 2012 ; Krupa et al., 2014 ; Carrel et al., 2017 ). Although information on growth on meat products is limited, Phillips et al.…”
Section: Assessmentsupporting
confidence: 64%
“…Prevalence rates for S. aureus of 64%, 20% and 17% were reported in raw beef, sheep and lamb samples at retail with an overall prevalence of 21% (S ¸anlıbaba, 2022). Similar studies in the United States of America, Japan and Poland isolated this bacterium from 28%, 33% and 68%, respectively (Hiroi et al, 2012;Krupa et al, 2014;Carrel et al, 2017). Although information on growth on meat products is limited, Phillips et al (2012) reported that 9% of beef primals for dry-ageing were contaminated with S. aureus and Yu et al (2020) predicted these bacteria would grow on vacuum packaged beef achieving 6 log 10 CFU/g after 100 h at 25°C.…”
Section: Staphylococcus Aureusmentioning
confidence: 65%
“…In microbiological analyses of eggs deriving from organic and free-range chicken farms, S. aureus was detected in 4 out of 300 (1.3%) samples (34), whereas eggs from conventional farms were positive for these bacteria at the level of 10.5% (23 out of 220 samples) (35). Carrel et al (5) tested meat from various retailers and also demonstrated a lower prevalence of S. aureus in organic samples (16.7%) compared to those from conventional production (35.1%). Similarly, Haskell et al (17) detected S. aureus at a higher level in raw poultry meat from conventional farms (27.4%) than in this meat from antibiotic-free farms (13%).…”
Section: Contamination With Staphylococcus Aureusmentioning
confidence: 99%
“…In beef, the prevalence of S. aureus is the heterogeneity, ranging from higher counts as 95.5% in China (Tong et al, 2015) and 62.5% in Indonesia (Diyantoro & Wradhana, 2019), to 27.8% in the United States of America (Carrel et al, 2017) and 24.5% in African countries (Thwala, Madoroba, Basson, & Butaye, 2021). This heterogeneity contamination can also be observed in Brazil with percentages ranging from 20% in Bahia and Mato Grosso states (Contreras, Silva, Ferreira, Ferreira, & Almeida, 2015; Costa et al, 2015; Saleh, El‐Mohsen, & Inrahim, 2016; Sousa, Cunha Neto, Hernandes, & Souto, 2012) to up to 43.75% in Amazonas state (Pieri, Vargas, Galvão, Nogueira, & Orlandi, 2016).…”
Section: Introductionmentioning
confidence: 99%